Pengaruh Penggunaan Media Interaktif Wordwall terhadap Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Pancasila di Kelas IV SDN Monta - Mila Septian Haryati; Solihin; Angela Berliani Saputri (Mataram University, 2026)
This study aimed to examine the effect of implementing the Wordwall interactive learning media on the learning achievement of fourth-grade elementary school students in the Pancasila Education subject, particularly on the topic Pancasila within Me. The study was motivated by preliminary classroom observations and teacher interviews conducted at SDN Monta on February 28, 2025, which revealed that students' learning outcomes were relatively low due to the absence of interactive learning media in the instructional process. A quasi-experimental approach employing a nonequivalent control group design was adopted. The study involved a purposive sample of 34 fourth-grade students, equally assigned to an experimental group (Class IV A, n = 17) and a control group (Class IV B, n = 17). Data were collected using an objective multiple-choice achievement test and analyzed through inferential statistics. The findings demonstrated that the implementation of Wordwall significantly improved students' learning outcomes. The experimental group achieved a mean post-test score of 84.71, substantially higher than the control group's mean score of 68.24. Furthermore, the independent samples t-test yielded a significance value (Sig. 2-tailed) of 0.000, which was lower than the significance level of 0.05, confirming a statistically significant difference between the two groups. These findings indicate that the use of Wordwall as an interactive learning medium has a positive and significant effect on improving students' academic achievement in Pancasila Education at the elementary school level.